Reconstructing Islamic Education In Schools In Response To The Challenges Of Globalization And Digital Transformation - Kurnia Alex; Fitriani Muh Amin; Juhariati Juhariati; Misbah Misbah; Amaluddin Amaluddin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Globalization and digital transformation have fundamentally reshaped social, cultural, technological, and educational landscapes. As key institutions for Islamic learning, schools face the dual challenge of preserving Islamic values while responding to rapid advances in science, technology, and the evolving characteristics of contemporary learners. Islamic education can no longer be viewed merely as a process of transmitting religious knowledge; instead, it must be reconstructed into an educational system capable of cultivating students who are spiritually grounded, morally responsible, critically minded, adaptable, digitally literate, and able to engage constructively in an increasingly interconnected global society. This article aims to analyze the need for reconstructing Islamic education in schools in response to the challenges of globalization and digital transformation. The study employed a qualitative descriptive literature review. Data were collected from peer-reviewed journal articles, scholarly books, and relevant research publications addressing Islamic education, globalization, digital transformation, pedagogy, digital literacy, character education, and teacher competencies. The data were analyzed through systematic stages of identification, selection, classification, interpretation, and thematic synthesis. The findings reveal five major dimensions of reconstruction. First, Islamic education should shift its orientation from knowledge transmission toward the development of comprehensive Islamic competencies and contextual character formation. Second, the curriculum should be redesigned through the integration of Islamic values, scientific knowledge, technological advancement, and contemporary global realities. Third, Islamic Religious Education (IRE) teachers are expected to possess integrated pedagogical, digital, religious, and ethical competencies. Fourth, digital technology should be utilized as a pedagogical instrument while remaining firmly grounded in Islamic values and ethical principles. Finally, strengthening Islamic education requires a collaborative educational ecosystem involving schools, families, communities, and digital environments. The study concludes that reconstructing Islamic education does not entail abandoning its intellectual traditions but rather recontextualizing Islamic values to ensure their continued relevance in addressing the challenges of globalization and digital transformation.